2021
DOI: 10.3389/fphar.2021.641530
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Modern Clinical Applications of Fuzi and Fuzi-Based Formulas: A Nationwide Descriptive Study With Market Basket Analysis

Abstract: Background: As time evolved, traditional Chinese medicine (TCM) became integrated into the global medical system as complementary treatments. Some essential TCM herbs started to play a limited role in clinical practices because of Western medication development. For example, Fuzi (Aconiti Lateralis Radix Praeparata) is a toxic but indispensable TCM herb. Fuzi was mainly used in poor circulation and life-threatening conditions by history records. However, with various Western medication options for treating cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Fuzi uses in reasonable doses and time has been shown to be of clinical value in saving dying lives in Chinese history. 37 However, although several published studies have shown that the aqueous extract of Fuzi is involved in the generation and removal of oxygen radicals and reduced apoptosis in Wistar rats and SH-SY5Y cells, respectively, 7 why Fuzi is related to the therapeutic effects of vascular aging diseases is still unknown, especially which compound of Fuzi plays a crucial role in vascular aging has not been reported. Moreover, due to the complex chemical components, it remains challenging to elucidate the precise pharmacological mechanisms of Fuzi in treating VS.…”
Section: Discussionmentioning
confidence: 99%
“…Fuzi uses in reasonable doses and time has been shown to be of clinical value in saving dying lives in Chinese history. 37 However, although several published studies have shown that the aqueous extract of Fuzi is involved in the generation and removal of oxygen radicals and reduced apoptosis in Wistar rats and SH-SY5Y cells, respectively, 7 why Fuzi is related to the therapeutic effects of vascular aging diseases is still unknown, especially which compound of Fuzi plays a crucial role in vascular aging has not been reported. Moreover, due to the complex chemical components, it remains challenging to elucidate the precise pharmacological mechanisms of Fuzi in treating VS.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in the combination of Fuzi and Astragali radix, astragalus polysaccharide can not only enhance the function of the immune system, but also prevent and treat atherosclerosis, and enhance the therapeutic effect of Fuzi. In addition, through the exploration of Tai et al (2021) , some innovative herbal pairs were found, such as the effect of Fuzi and Ziziphi spinosae semen combination in the treatment of neurological diseases, the effect of Salviae miltiorrhizae radix et rhizoma and Fuzi combination in the treatment of cardiovascular diseases, and the effect of Fuzi in the treatment of cardiovascular diseases was enhanced by Corydalis rhizoma, Cyathulae radix, and Eucommiae cortex. The discovery of these herbal pairs suggests that Fuzi has a broader application, and it is necessary to further explore the specific mechanism of its action.…”
Section: Clinical Application Of Fuzi On Cardiotonic Effectmentioning
confidence: 99%
“…In this study, association rules mining is used to discover association relationships in transactional databases, and there are different application scenarios, such as Chinese medicine prescription data ( 23 ) and disease clinical symptom data ( 24 ). Similarly, there are wide applications in the field of bioinformatics ( 25 ), such as probing gene expression patterns in specific cells ( 26 ), identifying associated genes in gene expression and methylation data ( 27 ), and cancer co-expression gene module detection ( 28 ).…”
Section: Introductionmentioning
confidence: 99%